Return to preinjury levels of participation after superior labral repair in overhead athletes: a systematic review - Sciascia, A.; Myers, N.; Kibler, W. B.; Uhl, T. L. (Journal of Athletic Training, 2015)
Context: Athletes often preoperatively weigh the risks and benefits of electing to undergo an orthopaedic procedure to repair damaged tissue. A common concern for athletes is being able to return to their maximum levels of competition after shoulder surgery, whereas clinicians struggle with the ability to provide a consistent prognosis of successful return to participation after surgery. The variation in study details and rates of return in the existing literature have not supplied clinicians with enough evidence to give overhead athletes adequate information regarding successful return to participation when deciding to undergo shoulder surgery.